An Analysis of Occupational Stress and Its Impact on Employees’ Absenteeism among Spinning Mills, Rajapalayam (International Journal of Scientific Research and Management (IJSRM), 2017)
Occupational stress has a significant impact on employees’ productivity and affects the organizational performance by increasing absenteeism and which affects the organization negatively. The aim of the study is to find out the causes of occupational stress within the organization and the impact on absenteeism and job satisfaction. A total of 502 employees’ from different departments in manufacturing is taken as sample of study. Data was collected by using questionnaire with background questions, job stress such as role conflict and ambiguity, lack of participation in decision making, lack of authority, workload and interpersonal relationships and statements about the effect on organizational performance. Then this study helps to determine the most inducing stressors among employees’ which lowers employees’ performance in the organization. The external factor is beyond the control of organization. The findings showed that occupational stress does not have a direct impact on intention to leave and absenteeism. First organization need to increase job satisfaction by reducing occupational stress. By reducing stress, organizations preserve reducing the intention to leave and absenteeism.